Ketidakadilan Gender dalam Novel Yuni karya Ade Ubaidil - Yhola Lavenia Evelin; Muhammad Ismail Nasution (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
Gender injustice is treatment received by one gender which causes unfair treatment. These forms of injustice include marginalization, subordination, stereotypes, violence and double workloads. The purpose of this research is to describe how gender injustice is experienced by female characters in the novel Yuni by Ade Ubaidil. This type of research is literary research with a descriptive method. The data source in this research is Ade Ubaidil's novel Yuni. Data collection techniques consist of in-depth reading, data marking, and data inventory. Data analysis techniques consist of classifying data, describing and interpreting data, and drawing conclusions. The results of the study found forms of gender injustice such as marginalization, subordination, stereotypes, violence and double workload for main female characters.